The impact of technology on job characteristics and internal motivation: a study Of instructors in institutions of higher learning in Malaysia - Juhdi, Nurita; Abd Hamid, Ahmad Zohdi; Siddiq, Mohd Saeed (IJAS, 2010)
Application of technology in education has gained impetus and offers exciting prospects and new challenges. Policy makers, educational institutions and corporate sectors are committed to realizing the potential benefits of technology. Nonetheless, given huge investments made in setting up technology-based educational environment, research indicates that instructors report mixed views on how the use of technology affects their jobs and work outcomes. Prior studies that examined technology impact on instructors and the multiple roles associated to teaching were conducted mainly using qualitative research method, and this necessitates a specific study that allows quantitative analysis. Specifically, the present study examines how technology influences instructors’ teaching job and their internal motivation. Given the multiple roles that instructors have to perform, four major roles associated with teaching (pedagogical, managerial, technical and subject design) were examined. Data were collected using questionnaires that were distributed among instructors in public and private tertiary educational institutions in Malaysia. Questionnaires were sent using e-mails, regular mails and personal visits to potential respondents. Two hundred and ninety two respondents were finally generated. The findings indicated significant differences in technical role attributes among those using traditional, medium and pure e-learning technology. Another major finding was that technology levels have significant impact on internal motivation, after the managerial and technical role attributes make their individual contribution to the variance in internal motivation. This study has implications to theorists and practitioners. For theorists, it provides more empirical evidence for technology impacts on instructors’ teaching role attributes and internal motivation. For policy makers, few major areas require close re-examination particularly instructors’ teaching job design, training needs and performance evaluation.